2021
DOI: 10.5551/jat.57752
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Carotid Intima-Media Thickness in Association with Renal Outcomes

Abstract: We aimed to examine the association between the maximum intima-media thickness of the carotid artery (Max IMT) and renal prognosis, considering their potential interaction with age. Methods: Survival analyses were performed in 112 patients with chronic kidney disease (CKD), to assess renal prognosis, with the endpoint defined as a ≥ 30% decline in estimated glomerular filtration rate (eGFR) or endstage renal disease. Results: During a median follow-up of 12.5 years, 44 participants reached the study endpoint. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…This signifies that patients receiving dialysis are at greater risk of developing atherosclerosis. This is in accordance with the published work of Manabe et al, 17 who reported a maximum IMT of ≥1.5 mm in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 93%
“…This signifies that patients receiving dialysis are at greater risk of developing atherosclerosis. This is in accordance with the published work of Manabe et al, 17 who reported a maximum IMT of ≥1.5 mm in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the relationship between eGFRcre and CAC progression may be affected by age and CVD risk factors. Furthermore, prognosis of CKD in association with intima media thickness was influenced by age 34) .…”
Section: Discussionmentioning
confidence: 99%
“…They can start autocatalytic reactions as a result of which the molecules to which they react are also converted into free radicals to continue the chain of damage 10 . ROS can be generated during metabolism of myeloperoxidase (MPO), nitric oxide synthase, nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, lipoxygenase pathway and enhanced ROS production as by-product electron transport chain reactions 11 .…”
Section: P R O V I S I O N a L L Ymentioning
confidence: 99%